Performance analysis of WIMAX-WLAN overlay networks using modified dynamic speed sensitive call admission control. (23rd September 2014) - Bharathi, V.; Nithyanandan, L.
The efficient call admission control (CAC) plays an important role in effective utilisation of integrated heterogeneous networks such as IEEE 802.11/wireless local area networks (WLANs) and IEEE 802.16/wireless microwave access (WiMAX). In this paper, modified dynamic speed sensitive CAC (MDSSCAC) is proposed and analysed for loose, tight and hybrid ring–based WiMAX-WLAN overlay networks. MDSSCAC effectively utilises available resources by admitting calls to proper network and enhances Quality of Service by dynamically varying bandwidth reservation for handoff calls based on traffic prediction. MDSSCAC assigns preference for the calls to admit either in WiMAX or in WLAN network based on velocity, location and service type of call. MDSSCAC avoids unnecessary handoff initiated by high–velocity users and effectively balances load between WiMAX and WLAN networks. MDSSCAC yields better performance compared with the existing speed sensitive CAC (SSCAC) and dynamic SSCAC (DSSCAC). The hybrid coupling provides better performance compared with other coupling.